Symplectic difference systems: oscillation theory and hyperbolic Prüfer transformation - Ondřej Došlý (Abstract and Applied Analysis)
We present basic methods of oscillation theory of symplectic difference systems (SDSs). A particular attention is devoted to the variational principle and to the transformation method. Hyperbolic Prüfer transformation for SDSs is established.